Miniaturized DNA Sequencers for Personal Use: Unreachable Dreams or Achievable Goals - Huo, Wenxing; Ling, Wei; Wang, Zilun; Li, Ya; Zhou, Mingxing; Ren, Miaoning; Li, Xueting; Li, Jiameng; Xia, Zhiqiang; Liu, Xinyu; Huang, Xian (Frontiers in Nanotechnology, 2021)
The appearance of next generation sequencing technology that features short read length with high measurement throughput and low cost has revolutionized the field of life science, medicine, and even computer science. The subsequent development of the third-generation sequencing technologies represented by nanopore and zero-mode waveguide techniques offers even higher speed and long read length with promising applications in portable and rapid genomic tests in field. Especially under the current circumstances, issues such as public health emergencies and global pandemics impose soaring demand on quick identification of origins and species of analytes through DNA sequences. In addition, future development of disease diagnosis, treatment, and tracking techniques may also require frequent DNA testing. As a result, DNA sequencers with miniaturized size and highly integrated components for personal and portable use to tackle increasing needs for disease prevention, personal medicine, and biohazard protection may become future trends. Just like many other biological and medical analytical systems that were originally bulky in sizes, collaborative work from various subjects in engineering and science eventually leads to the miniaturization of these systems. DNA sequencers that involve nanoprobes, detectors, microfluidics, microelectronics, and circuits as well as complex functional materials and structures are extremely complicated but may be miniaturized with technical advancement. This paper reviews the state-of-the-art technology in developing essential components in DNA sequencers and analyzes the feasibility to achieve miniaturized DNA sequencers for personal use. Future perspectives on the opportunities and associated challenges for compact DNA sequencers are also identified.